833 Evolution of sleep disordered breathing types in heart failure. (3rd May 2021) - Anne, Pratibha; Koothirezhi, Rupa; Okorie, Ugorji; Tam Ho, Minh; Monceaux, Brittany; Liendo, Cesar; Asghar, Sheila; Chernyshev, Oleg
Abstract: Introduction: Central sleep apnea is commonly seen in patients with heart failure. Here we present a case demonstrating shifting of predominant apneic events from central to obstructive type after placement of left ventricular assist device (LVAD) in end stage heart failure patient. Report of case(s): Case Presentation: 66 year-old African American male has past medical history of chronic congestive heart failure diabetes, hypertension, paroxysmal atrial fibrillation, anemia, hypothyroidism, chronic kidney disease and sleep apnea. Prior to his LVAD placement, his left ventricular ejection fraction (EF) was <10%. Patient was diagnosed with central sleep apnea with AHI of 58 (with 92% of apneic events being central events), oxygen nadir of 74%. Subsequently, patient had LVAD placed for symptomatic heart failure and repeat polysomnogram repeated at six month demonstrated an improved AHI of 45.8 with predominantly obstructive and mixed apneic events, with only 12.5% being central events. Conclusion: This case report highlights not only the improvement of the sleep apnea in CHF treated with LVAD but also shows the shift of apneic events from predominantly central to obstructive type post LVAD. Support (if any): 1. Henein MY, Westaby S, Poole-Wilson PA, Cowie MR, Simonds AK. Resolution of central sleep apnoea following implantation of a left ventricular assist device. Int J Cardiol. 2010 Feb 4;138(3):317–9. PMID: 18752859. 2. Köhnlein T, Welte T, Tan LB, Elliott MW. Central sleep apnoea syndrome in patients with chronic heart disease: a critical review of the current literature. Thorax. 2002 Jun;57(6):547–54. PMID: 12037232 3. Monda C, Scala O, Paolillo S, Savarese G, Cecere M, D'Amore C, Parente A, Musella F, Mosca S, Filardi PP. Apnee notturne e scompenso cardiaco: fisiopatologia, diagnosi e terapia [Sleep apnea and heart failure: pathophysiology, diagnosis and therapy]. G Ital Cardiol (Rome). 2010 Nov;11(11):815–22. Italian. PMID: 21348318.